2019
DOI: 10.3389/fnmol.2019.00170
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TRESK in Discrete Sensory Neuron Populations and Somatosensory Processing

Abstract: Two-pore domain K + (K 2P ) channels generate K + leak current, which serves a vital role in controlling and modulating neuronal excitability. This diverse family of K + channels exhibit distinct expression and function across neuronal tissues. TWIK-related spinal cord K + channel (TRESK) is a K 2P channel with a particularly enriched role in sensory neurons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 48 publications
7
39
0
Order By: Relevance
“…Another study reported similar results in TG neurons but, surprisingly, lumbar DRG neurons from the same TRESK KO mice were not found to be hyperexcitable (Guo et al 2019). Although we did not differentiate between IB4 + and IB4 − neurons in this study, our data support previous findings of enhanced excitability of nociceptive sensory neurons (small DRGs) either after TRESK deletion or after a significant decrease in its expression (Dobler et al 2007;Tulleuda et al 2011;Yang et al 2018;Weir et al 2019). These effects have been also found after a decreased TRESK expression in a functional TRESK[G339R] knockout mice (Dobler et al 2007;Kollert et al 2015), after sciatic nerve axotomy (Tulleuda et al 2011) or in a model of cancer-associated pain (Yang et al 2018).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Another study reported similar results in TG neurons but, surprisingly, lumbar DRG neurons from the same TRESK KO mice were not found to be hyperexcitable (Guo et al 2019). Although we did not differentiate between IB4 + and IB4 − neurons in this study, our data support previous findings of enhanced excitability of nociceptive sensory neurons (small DRGs) either after TRESK deletion or after a significant decrease in its expression (Dobler et al 2007;Tulleuda et al 2011;Yang et al 2018;Weir et al 2019). These effects have been also found after a decreased TRESK expression in a functional TRESK[G339R] knockout mice (Dobler et al 2007;Kollert et al 2015), after sciatic nerve axotomy (Tulleuda et al 2011) or in a model of cancer-associated pain (Yang et al 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Still, these effects could be underestimated by the fact that TRESK shows different levels of expression in different types of nociceptors (Usoskin et al 2015), so studying specific subpopulations of genetically labelled nociceptors (mainly non-peptidergic) might produce larger effects in excitability after TRESK deletion. In fact, a recently published characterization in TG neurons shows that TRESK is present in 73% of IB4 + non-peptidergic neurons, while only 29% of CGRP + neurons (mainly peptidergic nociceptors) express TRESK (Weir et al 2019). In agreement, IB4 + nociceptive TG neurons showed an enhanced excitability compared to IB4 − neurons.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations